NATIONAL POSTGRADUATE SYSTEM (SNPG) AND CHEMISTRY AREA AT THE BRAZILIAN FEDERAL AGENCY FOR POST-GRADUATE EDUCATION (CAPES) - Monteiro, Adriano L.; Furlan, Maysa [UNESP]; Suarez, Paulo A. Z. (Soc Brasileira Quimica, 2017)
The Coordination for the Improvement of High Education Personnel (CAPES), the Brazilian federal agency for graduate programs, plays a fundamental role for the expansion and consolidation of the National Postgraduate System (SNPG) and the execution of the National Graduate Plan (PNPG) 2011-2020. In this paper, we discuss the evolution of the Brazilian graduate program in chemistry and its role in the formation of highly qualified professionals in chemistry (academic master's degree, professional master's degree and doctoral degree) for the academy, teachers and lecturers for all levels of the education system, as well for the non-academic market.
Keywords: National Postgraduate System; CAPES; graduate programs; chemistry